Conceptual of Blended Learning as Islamic Education Study Program Learning Reform Action in Digital Era 4.0 - Setiawan, Agus (SYAMIL: Journal of Islamic Education, 2019)
This article focuses on the conceptual study of the blended learning model. This article also presents several studies from the online journal article and the findings of previous research from thesis and dissertations and textbooks relating to the theory of blended learning. As an effort to reformulate PAI learning, it is important to implement blended learning in the current digital era. Islamic religious education has a material source that is extensive and strategic for the progress of the Indonesian nation. With most Indonesia's population is the follower of Islam, Islamic religious education as millennial generation literacy is appropriate to be formulated under the development of digital technology. Islamic education can take a strategic role as the immunization of the young generation amidst the advancement of learning and innovation. Blended learning is one of them in future learning. Blended learning is one of the latest learning models that has been successfully applied to educational institutions. This study describes blended learning as an effort to reformulate PAI learning in the digital era 4.0. This study also aims to be a reference for further research. This research was conducted with the Systematic Literature Review (SLR) method of various research findings and the findings of journal articles relating to the blended learning. The findings of the study showed that the principle of blended learning synergize a balanced combination between face-to-face and online learning. It can apply blended learning to PAI learning and is quite successful. Using technology will strengthen the conventional methods that commonly occur in PAI learning so that PAI learning is more effective and efficient. Some research states that blended learning has motivated students in learning, enables students to be more creative, more active, more participatory, more communicative, independent and able to solve problems in learning, improving learning outcomes. We can conclude it that the results regarding blended learning are having a positive impact on student development and also on learning outcomes.